2021
DOI: 10.1172/jci142014
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident-like CD4+ T cells secreting IL-17 control Mycobacterium tuberculosis in the human lung

Abstract: T cell immunity is essential for the control of tuberculosis (TB), an important disease of the lung, and is generally studied in humans using peripheral blood cells. Mounting evidence, however, indicates that tissue resident memory T cells (Trm) are superior at controlling many pathogens, including Mycobacterium tuberculosis (Mtb), and can be quite different from those in circulation. Using freshly resected lung tissue, from individuals with active or previous TB, we identified distinct CD4 and CD8 Trm-like cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 107 publications
(173 reference statements)
1
74
0
Order By: Relevance
“…Activated and exhausted TRMs were found to be predominant at infection sites in TB patients ( 65 ). A very recent study identified the protective role of IL-17 producing TRM cell clusters in MTB infected human lungs ( 66 ). Further in vivo observations and correlates of protection to identify which immunological response(s) are essential are needed before development of new vaccines against MTB.…”
Section: Mycobacterium Tuberculosis and Bacille Calmette Guerinmentioning
confidence: 99%
“…Activated and exhausted TRMs were found to be predominant at infection sites in TB patients ( 65 ). A very recent study identified the protective role of IL-17 producing TRM cell clusters in MTB infected human lungs ( 66 ). Further in vivo observations and correlates of protection to identify which immunological response(s) are essential are needed before development of new vaccines against MTB.…”
Section: Mycobacterium Tuberculosis and Bacille Calmette Guerinmentioning
confidence: 99%
“…Both circulating T H 17 memory cells and T H 17 T RM cells are important to clear the C. albicans upon rechallenge, but T H 17 T RM cells are more effective in rapidly clearing the pathogens [87]. In Mycobacterium tuberculosis (M. tuberculosis)-infected patients, lung CD4 T RM cells produce IL-17 following antigenic stimulation, which along with IL-17 and IL-2 produced by T H 17 T RM cells suppress the growth of M. tuberculosis in 3D culture system [88].…”
Section: Heterogeneity Of Tissue-resident Cd4 T Cellsmentioning
confidence: 99%
“…Furthermore, both CD4 + and CD8 + human T RM cells have been characterised as capable of limiting intracellular Mtb survival ex vivo ( 70 ). A recent study using human samples also found that the frequency of Mtb-specific T RM -like cells that produce IL-17 in the lungs negatively correlated with IL-1ß levels in the blood, suggesting an important role for controlling Mtb growth ( 71 ). Additionally, mucosal vaccination could help activate other resident cells, such as γδ-T cells and mucosal-associated invariant T cells (MAIT), that also produce IL-17A ( 53 ).…”
Section: Correlates Of Protective Immunitymentioning
confidence: 99%